The Influence of Technology Readiness and Financial Literacy on the Financial Performance of MSMEs in Bojonegoro Through E-Commerce Adoption (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2024)
This study aims to determine whether the variable of e-commerce adoption can mediate the effect of technology readiness and financial literacy on the financial performance of MSMEs. The population in this study consists of MSMEs in the food and beverage trade sector in Bojonegoro Regency. The sampling technique employed in this research is purposive sampling, with the criteria being MSMEs in the food and beverage trade sector in Bojonegoro that have adopted e- commerce platforms. The sample size in this study is 44 respondents, with data collected using questionnaires. Data analysis was conducted using SPSS software version 22 and the Sobel Test. The results of this study indicate that technology readiness significantly affects e-commerce adoption, whereas financial literacy does not affect e-commerce adoption. Furthermore, the variables of technology readiness, financial literacy, and e-commerce adoption do not significantly affect financial performance, and e-commerce adoption cannot mediate the influence of technology readiness and financial literacy on financial performance.